Immobilized bacteria by using PVA (Polyvinyl alcohol) crosslinked with Sodium sulfate - Dinh Van Pham; Leu Tho Bach (Chemical Engineering Diponegoro University, 2014)
A new bacteria immobilization technique using PVA (polyvinyl alcohol) crosslink with sodium sulfate was developed. This new technique can simultaneously eliminate the agglomeration of PVA beads and the toxicity of boric acid caused by the PVA-boric methods, also reducing the swelling (when soaking in water) of PVA-boric methods. Beads were immobilized by using four different PVA immobilization processes to create group B, group N, group P and group S. The stability, swelling, relative mechanical strength of these kinds of beads were compared in this study. Only group S was the best and chosen to do experiment for checking survival of bacteria after immobilization process and TOC removal performance of anaerobic reactor. The TOC removal performance of anaerobic reactor achieved 80-87%.